Algorithms for DSP implementation in coherent optical systems - L. M. Pessoa (2008)
The electrical compensation of chromatic dispersion and polarization mode dispersion in acoherent optical system exploiting polarization multiplexing is discussed in this paper. Thebenefits of combining a phase estimation algorithm with a decision directed least-mean-squareequalizer in a feedback configuration is reported.